Comparison between self-etching and conventional primers in repeated bracket bonding - B Khosravani fard; A Fetrati; E Asadi (Islamic Azad University, 2017)
Background and Aim: This study aimed to evaluate the effect of repeated bonding by self-etching primers (SEPs) and a conventional phosphoric acid-etchant on shear bond strength (SBS), adhesive remnant index (ARI), and enamel morphology at different debonding time points. Materials and Methods: In this experimental study, 120 premolars were randomly divided into six groups of 20. In the first three groups, the brackets were bonded by Transbond XT, Transbond Plus, and Beauty Ortho Bond, and were debonded after 30 minutes. Adhesive remnants were removed from the enamel surface by a tungsten carbide bur. Rebonding was done with new brackets as described. The remaining three groups were debonded after aging. The SBS, ARI, and enamel surface morphology were evaluated. The SBS data were analyzed by two-way analysis of variance (ANOVA). The ARI scores were compared by using Mann-U-Whitney and Kruskal-Wallis tests. Results: The SBS of Transbond XT in the first debonding was significantly higher than that of Transbond Plus. Transbond Plus showed a higher SBS than Beauty Ortho Bond. In the second debonding, the SBS values of Transbond XT and Transbond Plus were not significantly different, but their SBS values were significantly higher than that of Beauty Ortho Bond. SEPs showed a higher bond strength in the second bonding compared to the first bonding. Scanning electron microscopy (SEM) showed more porosity in the enamel surface before the second bonding compared to the first bonding. The SBS of Beauty Ortho Bond significantly decreased after aging, and SEM images showed a gap at the resin-enamel interface. Conclusion: SEPs are recommended for secondary bonding in the clinical setting due to a decreased chair time, less damage to enamel, and an adequate bond strength.